The Analysis Of Marketing Communication Strategy at PT XYZ - Aris Hendrawan; Badriyah; Agung Edi Rustanto (Lead Journal of Economy and Administration, 2023)
Every company definitely wants to emerge as a champion in the midst of intense market competition. To achieve this, what can be done by a company is to carry out effective marketing or promotional communication activities in order to be able to target the right opportunities. This research has the objectives, among others, to find out the marketing communication strategy at PT XYZ along with the constraints faced and the solutions implemented. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and supported by literature studies. From the results of processing the data obtained, this study concluded that PT XYZ had carried out marketing communications activities both conventionally and digitally quite well. Various obstacles were encountered by PT XYZ, such as the lack of marketing communication activities to be carried out and adequate human resources. However, to overcome these obstacles, there are several solutions that can be implemented, for example implementing other forms of marketing communications, increasing the number of personnel, and increasing distributors at strategic points.